The In vitro Antibiotic Tolerant Persister Population in Burkholderia pseudomallei is Altered by Environmental Factors - Nierman, William C.; Yu, Yan; Losada, Liliana (Frontiers in Microbiology, 2015)
Bacterial persistence due to antibiotic tolerance is a critical aspect of antibiotic treatment failure, disease latency, and chronic or reemergent infections. The levels of persisters is especially notable for the opportunistic Gram-negative pathogens from the Burkholderia and Pseudomonas genera. We examined the rate of drug tolerant persisters in Burkholderia pseudomallei, Burkholderia thailandensis, Burkholderia cepacia complex organisms, and Pseudomonas aeruginosa at mid-log growth in LB broth culture. We found that a fraction of the antibiotic-sensitive cells from every species were tolerant to a 24 h high-dose antibiotic challenge. All tested Burkholderia strains demonstrated a drug tolerant persister population at a rate that was at least 100–500 times higher than P. aeruginosa. When challenged with at least a 10X minimum inhibitory concentration (MIC) 24 h exposure to three different antibiotics with different modes of action we found that in B. pseudomallei Bp82 each of the tree antibiotics revealed different persister fractions at each of two different growth states. This observation suggests that our assay is detecting heterogeneous persister subpopulations. Persistence in B. pseudomallei Bp82 was highly dependent on growth stage, with a surprisingly high persister fraction of >64% of the late stationary phase cells being antibiotic tolerant to 100XMIC cefotaxime. Adaptation of B. pseudomallei to distilled water storage resulted in a population of drug tolerant cells up to 100% of the non-drug-challenged viable cell count in the same cefotaxime assay. Cultivation of B. pseudomallei with a sub-inhibitory concentration of several antibiotics resulted in altered persister fractions within the population relative to cultures lacking the antibiotic. Our study provides insight into the sensitivity of the persister fraction within the population of B. pseudomallei due to environmental variables and suggests diversity within the persister population revealed by different challenge antibiotics.